The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1101/2020.07.28.225698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oscillation-based connectivity architecture is dominated by an intrinsic spatial organization, not cognitive state or frequency

Abstract: Functional connectivity (FC) of neural oscillations (~1-150Hz) is thought to facilitate neural information exchange across brain areas by forming malleable neural ensembles in the service of cognitive processes. However, neural oscillations and their FC are not restricted to certain cognitive demands and continuously unfold in all cognitive states. To what degree is the spatial organization of oscillation-based FC affected by cognitive state or governed by an intrinsic architecture? And what is the impact of o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…BDNF Val homozygotes also had stronger q synchronization within DAN and stronger left-hemispheric b synchronization between various subsystems, particularly involving DAN and DMN. This robust modulation of synchronization dynamics by BDNF polymorphism could contribute to significant differences across individuals in behavior and cognition, which have been shown to be strongly influenced by spatial and spectral characteristics of oscillatory synchronization (Betti et al, 2018;Mostame and Sadaghiani, 2020;Siebenhu ¨hner et al, 2020). However, large-scale synchronization was not influenced by COMT Val 158 Met polymorphism, although it has been shown that neuropharmacologically elevated levels of catecholamines are related to fMRI-based changes in functional connectivity (van den Brink et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BDNF Val homozygotes also had stronger q synchronization within DAN and stronger left-hemispheric b synchronization between various subsystems, particularly involving DAN and DMN. This robust modulation of synchronization dynamics by BDNF polymorphism could contribute to significant differences across individuals in behavior and cognition, which have been shown to be strongly influenced by spatial and spectral characteristics of oscillatory synchronization (Betti et al, 2018;Mostame and Sadaghiani, 2020;Siebenhu ¨hner et al, 2020). However, large-scale synchronization was not influenced by COMT Val 158 Met polymorphism, although it has been shown that neuropharmacologically elevated levels of catecholamines are related to fMRI-based changes in functional connectivity (van den Brink et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that the strongest effects of BDNF polymorphisms on global synchronization might not be due to a shifts in global excitation, but to other mechanisms such as the influence of BDNF on maintenance, maturation, and formation of neuronal networks (Park and Poo, 2013;Zagrebelsky and Korte, 2014) putatively via receptor TrkB (neurotrophic receptor tyrosine kinase 2) signaling (Castre ´n and Monteggia, 2021; Winkel et al, 2021). These could impact large-scale network synchronization via changes in structural connectivity (Mostame and Sadaghiani, 2020) or via changes in brain gray matter whose density has been shown to be associated with neuroreceptor and neurotransporter availabilities (Manninen et al, 2021) and whose thickness is associated with the structure of oscillatory networks (Mahjoory et al, 2020).…”
Section: Comt and Bdnf Influence Oscillation Via Impact On Brain Crit...mentioning
confidence: 99%
See 1 more Smart Citation